Keeping Hope Possible Toolkit: The Development and Evaluation of a Psychosocial Intervention for Parents of Infants, Children and Adolescents with Life Limiting and Life Threatening Illnesses - Jill M. G. Bally; Meridith Burles; Shelley Spurr; Lorraine Holtslander; Heather Hodgson-Viden; Roona Sinha; Marcelline Zimmer (MDPI AG, 2021)
Background: Globally, many infants and children are diagnosed with illnesses that impose limitations on their well-being and life course trajectory. Children's care becomes the central focus of family life. Inadequate support for parents is detrimental to their well-being and management of their child's care and support needs. Methods: The second phase of this evaluation study followed a quasi-experimental crossover design to test a theory-based psychosocial intervention, the Keeping Hope Possible Toolkit. Fifty-nine participants were randomly assigned to one of two sequence groups, with measures of hope, feelings of control, distress, and uncertainty completed pre- and post-intervention, and at a three-month follow-up. Qualitative interviews sought to assess participant experiences with the intervention, along with acceptability and feasibility. Results: Significant influence on parental distress was found, and the qualitative findings reveal benefits of the intervention for parental wellbeing. The intervention effectively offered practical and emotional support to diverse family caregivers. Conclusions: The evidence-informed KHP intervention can be used by healthcare providers to intervene with family caregivers to support their dynamic emotions including hope, need to live in the moment and remember self, and social preferences. In doing so, parents' critical caregiving activities can be sustained and their child's health and wellbeing optimized.